RISK FACTORS OF OCCURRENCE TUBERCULOSIS IN CHILDREN - Abdumanapova R.K. (Scholar Express Journals, 2024)
Tuberculosis in children is a multifactorial disease. Predisposition to tuberculosis can be explained by the presence of risk factors that often simultaneously affect the child's body. The most common risk factors are biomedical (infection, tuberculosis vaccination defects, presence of concomitant pathology), epidemiological (contact with a tuberculosis patient), geographical and environmental, age-sexual, social (unfavorable living conditions).
Keywords: tuberculosis; risk factors; children